MOTIVASI PETANI MENERAPKAN KEARIFAN LOKAL DALAM BUDIDAYA JAGUNG DI KELURAHAN WASOLANGKA KECAMATAN PARIGI KABUPATEN MUNA - Imal, Imal; Rianse, Usman; Hamzah, Awaluddin; Nalefo, La (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The application of local wisdom in corn cultivation is one of the traditions carried out by farmers from generation to generation until now. The application of this local wisdom is not done just like that, but is based on the farmers' motivation in carrying out this tradition in order to meet their needs. This study aims to determine the motivation of farmers to apply local wisdom in corn cultivation in Wasolangka Village, Parigi District, Muna Regency. Determination of informant s in this study were four corn farmers using the snowball technique. The data collection process was carried out by in-depth interviews, documentation and literature study. Data analysis in this study used a qualitative descriptive analysis. The results of the study show that the motivation of farmers to apply local wisdom in corn cultivation in the Wasolangka Village is still being carried out today, where this motivation can meet the needs of farmers consisting of motivational physiological needs, the need for a sense of security, social needs, the need for appreciation and the need for actualization self. While the stages of corn cultivation in local wisdom consist of location determination (deghondo tampa), land clearing (detambori), burning (desula), re-burning (derangka), fencing (deghala), rituals before planting (kaago-ago), planting (detisa ), maintenance (derawati kahitela), young corn (detumbu) and harvesting (detongka).